Effective Cable Sizing model for Building Electrical Services - M. Pratap Nair; K. Nithiyananthan (Institute of Advanced Engineering and Science, 2016)
This paper mainly focuses on the sizing of electrical cables (i.e.cross-sectional area) and its accomplishment in various international standards. Cable sizing methods are at variance across international standards. For example, International Electrotechnical Commission (IEC), National Electrical Code (NEC), British Standard (BS) and Institute of Electrical and Electronics Engineers (IEEE). The basic philosophy underlying any cable sizing calculation is to develop a procedure model on cable sizing. The main objective of this research work is to develop effective cable sizing model for building services.